Process or Outcome Focus? Understanding the Impact of Future Time Perspective on Advertising Effectiveness. Issue 1 (2nd January 2021) - Wu, Linwan; Park, Sun-Young; Ju, Ilyoung
Abstract: Process- and outcome-focused mental simulation has been widely adopted in creating advertising messages. Via two experiments, we investigated how chronological (Study 1) and incidental (Study 2) future time perspectives influence consumer responses to process- and outcome-focused advertisements. Study 1 discovered that older participants expressed more favorable ad attitudes and product attitudes when exposed to a process-focused advertisement compared to when exposed to an outcome-focused advertisement, while younger participants responded similarly to both advertisements. Study 2 revealed that participants primed with extensive time perspective expressed more favorable ad attitudes, service attitudes, and greater purchase intention when exposed to an outcome-focused advertisement than a process-focused advertisement. Participants primed with limited time perspective evaluated a process-focused advertisement more positively than an outcome-focused advertisement. Both theoretical and practical implications of these findings are discussed.